2015
DOI: 10.1074/jbc.m114.605287
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Apoptosis Regulator through Modulating IAP Expression (ARIA) Protects Blood Vessels from Atherosclerosis

Abstract: Background: Macrophages play central roles in the whole process of atherosclerosis. Results: ARIA regulates macrophage foam cell formation at least in part by modulating ACAT-1 expression. Conclusion: ARIA is a novel factor involved in the pathogenesis of atherosclerosis. Significance: Loss of ARIA ameliorated atherosclerosis by reducing macrophage foam cell formation; inhibition of ARIA may represent a new line of therapy against atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Intima/media ratio was calculated by the linear measurements of intima and media thickness. Sequential sections were stained with Masson's trichrome for evaluation of collagen and the characteristics of atherogenesis including inflammatory cell infiltration, medial fibrosis and necrotic core as previously described 17-19 .…”
Section: Resultsmentioning
confidence: 99%
“…Intima/media ratio was calculated by the linear measurements of intima and media thickness. Sequential sections were stained with Masson's trichrome for evaluation of collagen and the characteristics of atherogenesis including inflammatory cell infiltration, medial fibrosis and necrotic core as previously described 17-19 .…”
Section: Resultsmentioning
confidence: 99%
“…Littermate ApoE-KO mice were always used as controls for ApoE-KO/TERF2DN-Tg mice. For en face analysis, the entire aorta from the heart, extending 5 mm after bifurcation of the iliac arteries and including the subclavian right and left common carotid arteries, was removed, dissected, and stained with oil red-O 38 . The oil red-O-positive atherosclerotic lesion area was measured using the Image J software.…”
Section: Methodsmentioning
confidence: 99%
“…ACAT-1 plays a key role in the formation of foam cells by catalyzing the esterification of free cholesterol to form cytoplasmic lipid droplets. Matsuo K et al identified a new protein and showed that ARIA ( Figure 2 ) deficiency attenuated the activity of PTEN, thereby enhancing the activation of PI3K/Akt, reducing the expression of ACAT-1 and reducing the formation of foam cells ( Matsuo et al, 2015 ). Wang J demonstrated that in vitro , miR-223 ( Figure 2 ) reversed macrophage-mediated lipid deposition and the inflammatory response by activating PI3K/AKT-mediated TLR4-NF-κB signaling ( Wang J. et al, 2015 ).…”
Section: Pi3k-targeted Therapy In Atherosclerosismentioning
confidence: 99%